Comparison of empirical use of low dose aspirin and enoxaprin in the treatment of unexplained recurrent pregnancy loss - Juneja, Sunil Kumar; Tandon, Pooja; Kaur, Gagandeep; Kapoor, Bakul; Sidhu, Guneet Singh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Recurrent pregnancy losses have commonly been defined as three or more consecutive spontaneous pregnancy losses. About 1-2% of women suffer from recurrent miscarriages. The cause is multifactorial such as uterine anomalies, endocrine disorders, immunological causes, infections, chromosomal anomalies and maternal autoimmune diseases. In 50-60% of cases recurrent pregnancy losses, the cause remains unclear. Objective of this study was to compare the maternal and fetal outcome in patients with unexplained recurrent pregnancy loss treated with LMWH (Enoxaparin) vs Aspirin during pregnancy. Methods: Women with 3 or more pregnancy losses, aged between 18-40 years, booked for antenatal care and delivery in our hospital between January 2012 and December 2016 were followed till 6 months after delivery. Results: A total number of 146 women were assessed for eligibility. We had 62 women in Group A (aspirin group) and 84 women in Group E (enoxaparin group). Enoxaparin was given to all those ladies who had taken aspirin in previous pregnancies with no live outcome. Good neonatal outcome was observed with Enoxaparin. Conclusions: Live birth rates did not show significant difference between the two study groups. But empirical use of enoxaparin in patients with no live birth who have taken low dose aspirin in previous pregnancy had shown improved results, so enoxaparin should be used empirically as a first line agent in such cases.